Dynamics of the photosystem II photochemical activity in the developing Brassica nigra L. seeds - Smolikova, Galina; Lebedev, Vitaliy; Lopatov, Vasiliy; Timoshchuk, Valentina; Medvedev, Sergei (Biological Communications, 2015)
Dynamics of the PS II activity in the pod walls, seed coat and embryo cotyledons at early and middle maturation stages of Brassica nigra L. has been studied using the Junior-PAM fluorometer (Heinz Walz Gmbh, Germany). The maximum quantum yield Fv/Fm, effective quantum yield Y(II) and coefficient of photochemical fluorescence quenching qP have been evaluated. We demonstrated maturation-dependent fluctuation of the PS II activity in the different part of seeds: Fv/Fm, Y(II) and qP decreased in the pod walls and seed coat, but increased in the cotyledons of embryo. During transition from early to middle stage of maturation, the maximal electron transport rate of PS II in the cotyledons increased and reached the maximum at higher level of photosynthetic active radiation. Improving the efficiency of PS II in the developing cotyledons of the embryo can be attributed to adaptation of the chloroplasts to a higher light probably due to the increase of light transmission through the seed coat and pericarp at later stages of seed maturation. Refs 29. Figs. 3.